Examining the Operator Learning Curve for Percutaneous Coronary Intervention of Chronic Total Occlusions: A Report From the National Cardiovascular Data Registry. (August 2019) - Young, Michael N.; Secemsky, Eric A.; Kaltenbach, Lisa A.; Jaffer, Farouc A.; Grantham, James A.; Rao, Sunil V.; Yeh, Robert W.
Abstract : Background: Advances in chronic total occlusion percutaneous coronary intervention (CTO PCI) techniques have led to increased procedural success rates among operators. While utilization of CTO PCI has disseminated widely, the learning curve for new operators has not been well-defined. Methods: Between July 2009 and December 2015, 93 875 CTO PCI cases were extracted from the CathPCI Registry. We delineated a cohort of new CTO operators performing <10 CTO PCI cases per given year. In-hospital outcomes for subsequent CTO PCIs were stratified by the number of prior cases accrued by each operator. Multivariable regression models were used to estimate differences in outcomes with increasing experience. The primary outcome was major adverse cardiovascular events defined as the composite of death, myocardial infarction, stroke, tamponade, or urgent coronary artery bypass grafting. Results: Among 70 916 cases performed by 7251 new operators, procedure success rate was 61.4% and major adverse cardiovascular event rate was 4.2%. Meanwhile, the rate of major bleeding was 4.0%, myocardial infarction 2.0%, mortality 0.6%, tamponade 0.3%, and renal failure 0.2%. Adjusted regression models demonstrated piecewise linear improvements in guidewire crossing, stent placement, and procedure success with accrued volume, albeit with increased contrast use, fluoroscopy time, and bleeding. Major adverse cardiovascular event rates were stable beyond the 12th case (odds ratio per 5 case increase 1.00; 95% CI, 0.98–1.03, P =0.7980). Conclusions: Among a large number of new CTO PCI operators in the United States, there exists an experiential learning curve for procedural success. However, there were higher rates of bleeding despite case experience, while major adverse cardiovascular events remained relatively unchanged after initiation. Abstract : Supplemental Digital Content is available in the text.